2008
DOI: 10.1523/jneurosci.0238-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Discontinuous Tonotopic Organization in the Inferior Colliculus of the Rat

Abstract: Audible frequencies of sound are encoded in a continuous manner along the length of the cochlea, and frequency is transmitted to the brain as a representation of place on the basilar membrane. The resulting tonotopic map has been assumed to be a continuous smooth progression from low to high frequency throughout the central auditory system. Here, physiological and anatomical data show that best frequency is represented in a discontinuous manner in the inferior colliculus, the major auditory structure of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
130
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 47 publications
14
130
1
2
Order By: Relevance
“…rat (Malmierca et al 2008). For all of the stimuli, our bandwidths of 0.15 octave SD for 10 kHz and 0.11 octave SD for 20 kHz were much smaller than the expected bandwidths of each isofrequency lamina (i.e., 0.28 or 0.29 octave) and support the conclusion that the BFmatched sites were within a given 10-or 20-kHz lamina.…”
Section: Acoustic Stimulisupporting
confidence: 68%
“…rat (Malmierca et al 2008). For all of the stimuli, our bandwidths of 0.15 octave SD for 10 kHz and 0.11 octave SD for 20 kHz were much smaller than the expected bandwidths of each isofrequency lamina (i.e., 0.28 or 0.29 octave) and support the conclusion that the BFmatched sites were within a given 10-or 20-kHz lamina.…”
Section: Acoustic Stimulisupporting
confidence: 68%
“…A tungsten electrode (1-2 M⍀) (Merrill and Ainsworth, 1972) was used to record extracellular single-unit responses. Stimuli were delivered through a sealed acoustic system (Rees, 1990;Malmierca et al, 2005Malmierca et al, , 2008 using two electrostatic loudspeakers (EC1, Tucker-Davis Technologies) driven by two ED1 (Tucker-Davis Technologies) modules. All stimuli were generated and delivered to the contralateral ear using TDT System 2 (Tucker-Davis Technologies) hardware and custom software (Malmierca et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The highest frequency produced by this system was limited to 40 kHz. The second and third harmonic components in the signal were Ն40 dB below the level of the fundamental at the highest output level (Malmierca et al, 2008(Malmierca et al, , 2009. Action potentials were recorded with a BIOAMP amplifier (Tucker-Davis Technologies), the 10ϫ output of which was further amplified and bandpass filtered (PC1, Tucker-Davis Technologies; between 0.5 and 3 kHz) before passing through a spike discriminator (SD1, Tucker-Davis Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different types of cells represented within the central nucleus (each characterised by distinct electrophysiological properties and discharge patterns) enable highly precise representation of complex auditory signals (Peruzzi et al, 2000). Animal studies have shown that the central nucleus receives ascending (bottomeup) projections from various brainstem nuclei (summarised in Baumann et al, 2011) e including the dorsal and posterior ventral cochlear nucleus (Warr, 1969;Oliver, 1984) e and is tonotopically organised along the dorsoeventral axis (Schreiner and Langner, 1997;Malmierca et al, 2008;Baumann et al, 2011;Cheung et al, 2012). Evidence for a tonotopic organisation within the central nucleus has been found in humans as well, where high-resolution functional magnetic resonance imaging has identified a dorsolateral-to-ventromedial gradient preferentially responding to low-to-high frequencies (De Martino et al, 2013).…”
Section: Inferior Colliculusmentioning
confidence: 99%